Electrophysiological methods to assess psycho-emotional state of a person based on medical nanosensors; Физико-технические проблемы в науке, промышленности и медицине - Nguyen Dang Quang (Физико-химические и изотопные технологии в науке, промышленности и медицине, 2016)
Заглавие с экрана